أثر الادارة الاستراتجية في أداء المؤسسة العامة: دراسة حالة مؤسسة سونلغاز الأغواط - برنو سهام; براهيمي عائشة; نور الدين هناء (جامعة عمار ثليجي -الأغواط, 2022)
This study aimed to know the extent of the impact of strategic management in improving the performance of the institution, and from here it was recognized what strategic management is in addition to the nature of performance, in order to be able to answer the problem of the subject represented in: What is the impact of strategic management on the performance of the Sonelgaz Corporation? Where we discussed the definition of the concepts of both strategic management and performance, as well as knowing the extent to which strategic management contributes to improving the performance of the institution by focusing on performance indicators. The data was collected based on the questionnaire that targeted the employees of the Sonelgaz Foundation in Laghouat, where (56) questionnaires were distributed to a sample of the study community, and (54) questionnaires were returned and the questionnaire data was analyzed using the statistical package for social sciences program (spss.26.0). The study reached a set of results that highlight the contribution of strategic management to improving the performance of the Sonelgaz Corporation. On the other hand, the results showed a convergence of the responses of the study sample members about the level of application of strategic management. This is due to the fact that the study sample members are from the same category in addition to the recent adoption of strategic management at the level of Sonelgaz Corporation and the majority agree that its application is highly efficient and effective. key words: Strategic management, enterprise performance, Sonelgaz Corporation.